2021
DOI: 10.1007/s00508-021-01985-x
|View full text |Cite
|
Sign up to set email alerts
|

12-month SARS-CoV-2 antibody persistency in a Tyrolean COVID-19 cohort

Abstract: Summary Background Short-term antibody response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been shown previously. The further development remains to be determined. Methods We prospectively followed 29 coronavirus disease 2019 cases, mean age 44 ± 13.2 years. Except for one participant in whom rheumatoid arthritis existed, all other cases were previously healthy. We determined anti-viral binding antibodies at 2–10 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Titers of IgG targeting the RBD appear to be very robust over time, as shown by a longitudinal study from Switzerland with a progressive increase in titers at 1, 3, and 6 months PSO 28 . An Austrian study found that even after 12 months, antibodies against the RBD persisted in all cases with increasing concentrations 29 . Our study involved the detection of IgG directed nonspecifically against various epitopes of the S1 and S2 subunits of the S protein.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Titers of IgG targeting the RBD appear to be very robust over time, as shown by a longitudinal study from Switzerland with a progressive increase in titers at 1, 3, and 6 months PSO 28 . An Austrian study found that even after 12 months, antibodies against the RBD persisted in all cases with increasing concentrations 29 . Our study involved the detection of IgG directed nonspecifically against various epitopes of the S1 and S2 subunits of the S protein.…”
Section: Discussionmentioning
confidence: 82%
“… 28 An Austrian study found that even after 12 months, antibodies against the RBD persisted in all cases with increasing concentrations. 29 Our study involved the detection of IgG directed nonspecifically against various epitopes of the S1 and S2 subunits of the S protein.…”
Section: Discussionmentioning
confidence: 99%